Efficacy and Safety of Switching to Dolutegravir/Lamivudine Fixed-Dose 2-Drug Regimen vs Continuing a Tenofovir Alafenamide–Based 3- or 4-Drug Regimen for Maintenance of Virologic Suppression in Adults Living With Human Immunodeficiency Virus Type 1: Phase 3, Randomized, Noninferiority TANGO Study. (6th January 2020) - van Wyk, Jean; Ajana, Faïza; Bisshop, Fiona; De Wit, Stéphane; Osiyemi, Olayemi; Portilla Sogorb, Joaquín; Routy, Jean-Pierre; Wyen, Christoph; Ait-Khaled, Mounir; Nascimento, Maria Claudia; Pappa, Keith A; Wang, Ruolan; et al.
Abstract: Background: The 2-drug regimen dolutegravir (DTG) + lamivudine (3TC) is indicated for treatment-naive adults with human immunodeficiency virus type 1 (HIV-1). We present efficacy and safety of switching to DTG/3TC in virologically suppressed individuals. Methods: TANGO is an open-label, multicenter, phase 3 study that randomized adults (1:1, stratified by baseline third agent class) with HIV-1 RNA <50 copies/mL to switch to once-daily fixed-dose DTG/3TC or remain on a tenofovir alafenamide (TAF)–based regimen. The primary end point was proportion of participants with HIV-1 RNA ≥50 copies/mL at week 48 (US Food and Drug Administration Snapshot algorithm) in the intention-to-treat–exposed population (4% noninferiority margin). Results: 743 adults were enrolled; 741 received ≥1 dose of study drug (DTG/3TC, N = 369; TAF-based regimen, N = 372). At week 48, proportion of participants with HIV-1 RNA ≥50 copies/mL receiving DTG/3TC was 0.3% (1/369) vs 0.5% (2/372) with a TAF-based regimen (adjusted treatment difference [95% confidence interval], −0.3 [−1.2 to .7]), meeting noninferiority criteria. No participants receiving DTG/3TC and 1 receiving a TAF-based regimen met confirmed virologic withdrawal criteria, with no emergent resistance at failure. Drug-related grade ≥2 adverse events and withdrawals due to adverse events occurred in 17 (4.6%) and 13 (3.5%) participants with DTG/3TC and 3 (0.8%) and 2 (0.5%) with a TAF-based regimen, respectively. Conclusions: DTG/3TC was noninferior in maintaining virologic suppression vs a TAF-based regimen at week 48, with no virologic failure or emergent resistance reported with DTG/3TC, supporting it as a simplification strategy for virologically suppressed people with HIV-1. Clinical Trials Registration: NCT03446573. Abstract : Switching to dolutegravir/lamivudine was noninferior in maintaining virologic suppression vs remaining on a tenofovir alafenamide–based regimen through 48 weeks, with no virologic failure or emergent resistance in the dolutegravir/lamivudine group, supporting its use in virologically suppressed individuals living with human immunodeficiency virus type 1.